Obstetric Recommendations in American Congress of Obstetricians and Gynecologists Practice Bulletins versus UpToDate: A Comparison - Myer, Emily N. B.; Too, Gloria T.; Hammad, Ibrahim A.; Babbar, Shilpa; Martin, Charley E.; Hill, James B.; Blackwell, Sean B.; Chauhan, Suneet P. (American Journal of Perinatology, 2015)
Objective To compare the obstetric recommendations in American Congress of Obstetricians and Gynecologists (ACOG) practice bulletins (PB) with similar topics in UpToDate (UTD).Study Design We accessed all obstetric PB and cross-searched UTD (May 1999–May 2013). We analyzed only the PB which had corresponding UTD chapter with graded recommendations (level A–C). To assess comparability of recommendations for each obstetric topic, two maternal–fetal medicine (MFM) subspecialists categorized the statement as similar, dissimilar, or incomparable. Simple and weighted kappa statistics were calculated to assess agreement between the two raters.Results We identified 46 ACOG obstetric PB and 86 UTD chapters. There were 50% fewer recommendations in UTD than in PB (181 vs. 365). The recommendations being categorized as level A, B, or C was significantly different (p < 0.001) for the two guidelines. While the overall concordance rate between the two MFM subspecialists was 83% regarding the recommendations for the same topic as similar, dissimilar, or incomparable, the agreement was moderate (kappa, 0.56; 95% confidence intervals, 0.48–0.65).Conclusion Though obstetricians have two sources for graded recommendations, incongruity among them may be a source of consternation. Congruent recommendations from ACOG and UTD could enhance compliance and potentially optimize outcomes.
Keywords: practice bulletins; UpToDate; obstetric recommendations; ACOG